The cultural content and intercultural communicative competence in the global and local textbooks used in Indonesian EFL classes - Noni Agustina; Nila Kencana (Journal on English as a Foreign Language, 2023)
A number of studies on the cultural content represented in local or global textbooks have increasingly been investigated. However, it is scanty research comparing local and global textbooks. This study aims to examine two textbooks determined by the Indonesian Ministry of Education and Culture, a global textbook entitled English in Mindfor schools implementing a new curriculum calledMerdekacurriculum and a local textbook,When English Rings a Bell,for schools that have not applied it. The study employed content analysis as a research design. The results show that the global textbook provides more on target culture, but the local textbook highly emphasizes source culture and neglects international cultures. In addition, the global textbook concerns social and environmental themes, while the local textbook focuses more on religion/humanities/art and personal theme. Further, the global textbook does not accommodate adequate intercultural communicative competence, which was absent in the local textbook. The imbalanced cultural representations in those textbooks affect students intercultural competence. The study suggests the practical implications of providing students with sufficient references to the target, source, and international cultures to promote their intercultural competence.